Les "bouilleurs de graisse", un titre inédit à Malqatta - Pinon, Marianne (Zeitschrift für ägyptische Sprache und Altertumskunde, 2023)
The Malqatta Palace was built in the vicinity of modern Luqsor for the celebrations of the first sed festival of Amenhotep III. This archaeological site is renowned for its decorations but also for the thousands of jar labels found. They provide valuable information concerning the food product, the date, the origin, the stewart responsible for the area and the associated titles, the person in charge of the preparation and, thus, his specific title. One of those jobs’ designation, "responsible for fat preparation", hasn’t been read accurately so far. This article aims to provide an answer to this shortcoming. This title, which seems attested only at Malqatta and during the last years of Amenhotep III, should read p/fs(w) ʿḏ and should be translated as "fat-boiler".